Through linguo-stylistic analysis to a new retranslation of the ballad “Hasanaginica“ - Arnautović Amina (ExELL (Explorations in English Language and Linguistics))
The new retranslation of the ballad “Hasanaginica” brings about an interpretation grounded in comprehensive scholarly research, which a linguo-stylistic analysis of both its source text (ST) and 25 published (re)translations represent. This retranslation is designed to make a notable difference reflected in its aspiration to achieve optimal equivalence on all levels of expression, minding its metrics, rhythm, sound figures, as much as its lexical choices and syntactic structures. One of the paper’s main aims is to compensate for the linguistic and stylistic flaws recognized in the previous translations of this ballad, which were not always erroneous deviations from a semantic correspondence, but interpretations informed by a fundamental incomprehension of the religio-cultural circumstances shaping the world of the ballad.